(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
OBJECTIVES: Meckel’s diverticulum, the most common congenital malformation in paediatric patients, usually presents with gastrointestinal bleeding. Nuclear medicine scintigraphy can detect heterotrophic gastric mucosa in Meckel’s diverticula. The aim of these case studies was to highlight the different scintigraphic patterns and presentations of Technetium (Tc) 99m pertechnetate scintigraphy of paediatric patients with gastrointestinal (GI) bleeding due to Meckel’s diverticulum with a view towards providing guidance in interpretation of variable positive results. CASE REPORTS: A retrospective image analysis was performed in 6 positive and complicated cases of Meckel’s diverticuli between January 2016 and October 2018. CONCLUSION: Diverse scan findings were observed. Apart from the usual anatomical location, few other areas like umbilical and para-umbilical regions were found to contain ectopic gastric mucosa. So, these regions should be observed meticulously while reporting. Bangladesh J. Nuclear Med. 22(1): 64-67, Jan 2019